Migrating Home Computer Audio Waveforms to Digital Objects: A Case Study on Digital Archaeology - Mark Guttenbrunner; Mihai Ghete; Annu John; Chrisanth Lederer; Andreas Rauber (International Journal of Digital Curation, 2011)
Rescuing data from inaccessible or damaged storage media for the purpose of preserving the digital data for the long term is one of the dimensions of digital archaeology. With the current pace of technological development, any system can become obsolete in a matter of years and hence the data stored in a specific storage media might not be accessible anymore due to the unavailability of the system to access the media. In order to preserve digital records residing in such storage media, it is necessary to extract the data stored in those media by some means.